New technologies and impact on occupational health (Revista Venezolana de Salud Pública, 2018)
Lots of pathologies of musculoskeletal origin in the industrial area have been caused by disergonomics conditions and companies have tried to solve this problem with large investments in acquiring last generation technologies. But is certainly the health issue that motivates such investments? Are certainly appropriate technologies that have been imported from other communities and not taking into account the local idiosyncrasies and phenotype? Investments in companies must be directed to the benefit of the worker and not only with the goal of profit. If not taken into account the worker in the process of purchasing new equipment or working methods, investments can be reversed in huge losses for companies not able to resolve the problem directly affects the health of the worker.
Keywords: Technology; health; Human engineer; Musculoskeletal Diseases